Formulation of Liquid Soap Preparations from Ethanol Extract of Cassava Leaves (Manihot Utilissima Polh) as Antibacterial Staphylococcus Aureus - Aida, Nur; Huda, Nurul; Barus, Rakhmad; Mauna, Satya Adira Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Formulated cassava leaves in liquid soap preparations that have antibacterial activity. This study aims to determine the best liquid soap preparation formula from ethanol extract of cassava leaves (Manihot utilissima Polh) by varying stearic acid by FI 0.5%, FII 0.10%, FIII 0.15% and antibacterial tests on Staphylococcus Aureus. Cassava leaves were macerated with 70% ethanol and tested for antibacterial activity using the disc diffusion method. In the evaluation of liquid soap preparations and antibacterial tests, the evaluation results of FII were obtained as the best formula with a variation of 0.10% stearic acid with evaluation results that met the requirements. In the antibacterial test, the inhibition zone for the control (+) using ciprofloxacin was 14.635 mm (strong) and FII 15.685 mm (strong).